Inhaler review in older adults with asthma or COPD: A cost-effectiveness study and a perspective in Portugal - Maricoto, Tiago (2019)
Older patients with asthma or chronic obstructive pulmonary disease are particularly susceptible to exacerbations that may be associated with incorrect use of inhalers. Educational programs with inhaler technique review seem to be effective, but no studies have addressed their cost-effectiveness in older adult patients. The objective was to perform a cost-effectiveness analysis of education programs in older patients and estimate the cost benefit of applying such a program in Portugal.